Design of Archimedes Screw Turbine by Multi-step Selections on Parameter Pitch Distance, Blade Number, and Blade Angle - Sarjito; Agus Dwi Anggono; Wijianto; Fauzan Anas Wirawan; Sidik Kurniawan; Bagus Dwi Nugroho (International Journal of Mathematical, Engineering and Management Sciences)
One of the water turbines called an Archimedes screw turbine (ASTs) is appropriate to run in a low head of just less than 5 m and works at a wide range of discharge operations. The performance of the turbine is influenced by some aspect that requires optimization. The research aims to characterize turbine performance by selecting the pitch distance of the blade, the number of blades, and the angle of the blade. Initiated by developing Archimedes screw turbine of 500 mm length and blade diameter of 100 mm, using screw blades at different distances of 50, 70, 100, 200, and 300 mm. Then continue to select blade numbers of 1, 2, and 3 respectively, while kept constant optimum distance of blade. Once the optimum number of blades and blade distance were achieved, followed by selecting blade angles of 23o, 28o, and 33o, the optimum blade distance and number were kept constant. Acquisition data developed covers turbine speed (rpm), voltage (V), current (A), and power (W) measurements. The result of the research was optimum blade achieved at blade distance of 100 mm, blade number of 1 and optimal blade angle of 28o, its produce debit of 0.0034 m3/sec at turbine speed of 410.77 rpm, voltage generator of 79.82V with current of 0.0067A, and power of 0.55 Watt in efficiency of 33%, coefficient of performance (Cp) of 0.33, as well as tip speed ratio (TSR) of 2.56.